Layout of node-link structures in space with negative curvature - Lamping, John O.; Rao, Ramana B. (1996)
Layout data indicate positions in a negatively curved layout space for nodes in a hierarchical branch of a node-link structure. The layout data indicate a parent position for parent nodes and, for children that share a parent node, child positions approximately along a circle in the layout space with the parent position approximately at the circle's center. Adjacent child positions are separated by approximately a base spacing. The radii of circles within the branch together approximate a function that increases slowly with number of child nodes such that the radii and spacings along circles are all approximately uniform within the branch. The layout data can be obtained from data defining the node-link structure. The layout data can be used to perform mappings, each obtaining positions for a subset of the nodes. The layout data can be used to present a first representation of the node-link structure on a display. In response to a user signal indicating a change from a first display position near a first feature to a second display position, a second representation can be presented that is perceptible as a changed continuation of the first. The second representation includes, near the second display position, a second feature representing the same part of the node-link structure as the first feature. The second representation can be obtained by a transformation of the layout space, which can be a discrete approximation of a hyperbolic plane.